APLIKASI INFORMASI TEMPAT PARIWISATA KEPULAUAN BANGKA BELITUNG BERBASIS ANDROID - Siti Khotijah; Juliana Juliana; Dewi Driyani (Jurnal Pelita Teknologi, 2019)
At present there are many areas of interest that are located in Bangka that is unknown and also not less interesting than other areas in Indonesia that are unknown to many people and most of them are only known through mouths, social media, like the internet where information is often incomplete and clear. This causes a lack of information about areas in the region that can be used as tourism sites. With such problems, it is expected that the design of an Android-based application can provide more information for the Bangka region. The main reason for using Android in making this application is because nowadays many people use smartphones to find information so that complete information can be obtained, especially for interesting areas in the region. The making of information applications in the tourist area of ​​the Bangka region uses survey methods and programs used in making this android-based application using the Appypie program and the tool used to make this application is the United Modeling Language (UML) and Flowchart and the results obtained from the research this is an application that provides information on areas in Bangka to be used as tourism spots based on Android. Keywords: Information application, bangka region, android